Conceptualisation of student under-preparedness and its efect on selection criteria for extended curriculum programs - Nxumalo, T. (South African Journal of Higher Education, 2025)
Student under-preparedness is a growing concern in higher education institutions (HEIs) around the globe. In South Africa, extended curriculum programs [ECPs] were devised as a context-fit remedial strategy to assist underprepared students to successfully transition into academia. As a result, under-preparedness is a key criterion for the selection of students into extended programs. Nonetheless, the concept of under-preparedness has not been accurately articulated. This research envisages a cascading effect, wherein the incoherence in the interpretation of under-preparedness endorses the inconsistencies in formulating the selection criteria for extended programs. The research used a case study approach, conducting in-depth interviews to ascertain how the conceptualisation of under-preparedness informs the selection of students for enrolment in extended programs at a University of Technology. To enhance the reliability of data, the results were triangulated using document analysis. The findings confirm the disparities in the conceptualisation of underpreparedness. Accordingly, the selection criteria reveal significant fragmentation, with some programs deviating from prescribed standards. The research proposes a holistic framework and provides valuable recommendations to assist the higher education institutions to streamline their programs to be fit-for-purpose.